Measles at The Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta 1993 - Siti Aisah Boediardja; Titi Lestari Sugito; Sri Rejeki Harun; Hindra Irawan (Paediatrica Indonesiana, 1997)
Expanded Programm of Immunization on measles in Indonesia has been implemented since 1985. The coverage of immunization at the first year was only (J.5%, increasing year by year and finally in 1990 its coverage was 80%. Retrospective study on secondary data of measles patients under 5 years of age who were hospitalÂized at the Department of Child Health/Dr. Cipto Mangunkusumo Hospital during 1993 is presented. The diagnosis was based on the clinical findings, such as fever, specific distribution of macula-papular skin eruption, and conjungtivitis. Total cases was 45 among 3348 (1.34%) hospitalized cases with case fatality rate (CFR) 8.9% (4 among 45 cases), This condition was similar to the condition in 1992, but was better Lhan die period of 1986-1991. The most common complications were bronchopneuÂmonia (25.2%), diarrhoea (6,5%), anemia (4.6%), encephalitis (3.7%). The cause of death were encephalitis (25%) and bronchopneumonia (11.1%), Measles immunizaÂtion coverage was only 24.4% patients. On summaiy, measles patients admitted to Cipto Mangunkusumo Hospital were severe cases and most of them were not covered by immunization.